Molecular and Pathogenic Characterization of Cylindrocarpon-like Anamorphs Causing Root and Basal Rot of Almonds - Nieves Capote; María Ángeles Del Río; Juan Francisco Herencia; Francisco Teodoro Arroyo (Plants, 2022)
Three almond nurseries were prospected in the South of Spain (Sevilla) to evaluate the sanitary status of the nursery plant material. Samples consisted of main roots, secondary roots and six-month-old basal stems ‘GxN-15’, ‘Nemaguard’, ‘Cadaman’, ‘Rootpac-40’ and ‘Rootpac-20’ rootstocks planted in the soil, and twigs of mother plants from ‘Lauranne’, ‘Guara’, ‘Marcona’, ‘Marta’ and ‘Ferragnes’ almond cultivars. Endophytic and potential pathogenic fungi were identified in mother plants and 70 Cylindrocarpon-like anamorph isolates were detected in the root system and basal stems of analyzed rootstocks. Based on partial sequencing of the his3 gene and multilocus phylogenetic analysis of the concatenated ITS, tub2, his3 and tef1-α partial sequences, seven Cylindrocarpon-like anamorph species were identified as Dactylonectria torresensis, D. novozelandica, D. macrodidyma, Ilyonectria liriodendri, Neonectria sp. 1, N. quercicola and Cylindrocladiella variabilis. Pathogenicity was assessed on young healthy detached twigs of ‘Guara’ almond cultivar and one-year-old ‘Lauranne’ potted almonds grafted onto ‘GxN-15’ rootstocks. Among the seven Cylindrocarpon-like anamorph species, I. liriodendri, Neonectria sp. 1 and N. quercicola were the most aggressive. Inoculated detached shoots developed necrotic lesions 15 days after inoculation. Inoculated trees showed sectorized necrosis in the main and secondary roots and the basal stem of the rootstock 5 months after inoculation. The most aggressive species were able to cause necrosis also in the grafted cultivar, and I. liriodendri, and N. quercicola also reduced the root biomass. This is the first report of Cylindrocarpon-like anamorph species causing root and basal rot of almonds.